English Language Teaching at Kindergarten: What Happens in The Classroom - Fikroni, Moh. Rofid (GENIUS: Indonesian Journal of Early Childhood Education, 2022)
This study aims to describe the English teaching and learning process for young learners in kindergarten. It used the descriptive qualitative research method. An observation checklist and field notes were used as the instruments to collect the data. The observation covers aspects of language teaching activities such as the students’ role, the teacher’s role, classroom management strategy, approach, technique, materials, tasks, language used, teacher-student interaction, and students’ participation. This study suggested that the English teaching and learning process at Pertiwi Kindergarten can be considered sufficient. It has satisfactorily met 62% of the aspects measured. Some of the highlights of this study are that the TPR method and songs are highly recommended as teaching techniques. Moreover, understanding the characteristics of the young learners is very important for the success of the teaching and learning activities.